COVID-19: students’ perception of e-learning & e-assessment platforms utilised in pharmacology curriculum delivery / Suraya Suratman - Suratman, Suraya; Ali, Aida Azlina; Abd Latip, Normala; Halim, Hasseri; Ramli, Salfarina; Mahamood, Maziana; Hazizul Hasan, Mizaton; Mustaffa, Mohd Faiz (Universiti Teknologi MARA, Sabah, 2021)
The COVID-19 pandemic has resulted in the move to open and distance learning (ODL) mode for all higher education institutions in Malaysia. This has also impacted the curriculum delivery for B.Pharm students at the Faculty of Pharmacy, Universiti Teknologi MARA. Although there has been a gradual shift in health-related education delivery over the past decade, with e-learning being increasingly utilised, this was mostly meant to be a supplement to conventional face-toface teaching methods. The untimely change brought upon by the pandemic has resulted in several challenges, including inadequacy of ICT infrastructures and unpreparedness in curriculum delivery. Pharmacology is a fundamental component of the undergraduate pharmacy curriculum. The extensive amount of knowledge to be delivered and learnt, as well as the hurdles of delivering it completely through the ODL mode rendered an already complex subject even more challenging to teachers and students alike. After more than a semester of ODL, evaluation and optimisation of learning needs to be carried out. Regular curriculum review and reassessments of existing teaching delivery methods are important in ensuring that the learning process is as effective as possible to adequately prepare pharmacy graduates. An important factor to be considered in curriculum review is students’ perception of their educational experience. One of the very basic necessities of ODL is ensuring that a decent online platform is utilised for curriculum delivery. This research assessed students’ views on e-learning implementation, focusing on their perception of the suitability of online learning platforms used in pharmacology courses in the B.Pharm (Hons) programme during the COVID-19 period. Google Classroom is ranked highest in terms of suitability, followed by Gradescope and YouTube. The findings of this study will facilitate the faculty and content developer in making a more informed decision when improving the online-learning process.